2015
DOI: 10.1177/2156587215577675
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double Blind Clinical Trial on a Sabgh Formulation for Patients With Vitiligo

Abstract: Background. The cosmetic problem that vitiligo produces affects patients psychologically. Many patients with vitiligo are suggested to cover their white skin patches with cosmetic products. There are formulations in traditional Iranian pharmacy to color these white skin patches. In this study, one of these formulations was compared with a cosmetic formulation. Methods. Two groups of patients were selected. One group used a marketed formulation and other group used a traditional Iranian Pharmacy formulation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In general, most interventions significantly improved QoL at end of follow‐up compared with baseline 25 , 43 , 45 , 47 , 50 , 54 , 57 , 70 , 71 , 72 , 73 , 86 , 89 , 90 , 93 , 104 , 105 , 108 , 112 , 134 , 136 , 144 ; however, differences between treatment comparators within studies were rarely reported as significant. DLQI was used in the majority (23/33) of interventional studies 25 , 43 , 45 , 47 , 50 , 54 , 56 , 57 , 63 , 70 , 71 , 72 , 73 , 86 , 89 , 90 , 91 , 93 , 98 , 101 , 104 , 105 , 108 ; meaningful score changes (4‐point score reduction) 150 were achieved with ≥1 treatment arm in 10 studies. 25 , 45 , 47 , …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In general, most interventions significantly improved QoL at end of follow‐up compared with baseline 25 , 43 , 45 , 47 , 50 , 54 , 57 , 70 , 71 , 72 , 73 , 86 , 89 , 90 , 93 , 104 , 105 , 108 , 112 , 134 , 136 , 144 ; however, differences between treatment comparators within studies were rarely reported as significant. DLQI was used in the majority (23/33) of interventional studies 25 , 43 , 45 , 47 , 50 , 54 , 56 , 57 , 63 , 70 , 71 , 72 , 73 , 86 , 89 , 90 , 91 , 93 , 98 , 101 , 104 , 105 , 108 ; meaningful score changes (4‐point score reduction) 150 were achieved with ≥1 treatment arm in 10 studies. 25 , 45 , 47 , …”
Section: Resultsmentioning
confidence: 93%
“…The DLQI was administered in 80 studies 15 , 21 , 22 , 25 , 26 , 28 , 30 , 35 , 36 , 37 , 38 , 39 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ...…”
Section: Resultsunclassified
See 3 more Smart Citations